SIKAP PELAJAR SEBAGAI PENGENDARA SEPEDA MOTOR TERHADAP KEPATUHAN BERLALU LINTAS DI SMP NEGRI 25 PEKANBARU - Melta Meilyna; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Motorcycle is the most common vehicle the used by indonesian people. One of the children under 17 yearshave been riding motorcycles. Traffic accident are still being global issue which is motorcyle is the largest contributor of traffic accident can be eitherfatalities or material losses, traffic accident are mostoccur to youngpeoples, in Indonesia the biggest victim or traffic accident are junior high school students. Unsafe ridding is the biggest couse of traffic accident, therefore safety riding need to be applied to pevent traffic accident .The purpose of this study is (1) aims to find what are the factors thatmake student use motorcycle to school. (2) to find the impact of traffic violations by using attitude theory. The method of this research is desciptive quantitative and data collecting use question forl , observation,documentation 64 sample use simple rendom sampling. Result of the research showr that most of students ride motorcycle in is years old. There are 3 factors that make studends of state junior high school 25 Pekanbaru ride motorcycle are parents, him/her self, and environtmentKeywords: Students, Motorcycle Ryder Towards, Traffic